2009
DOI: 10.1186/1757-7241-17-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of penetrating pulmonary injuries

Abstract: Chest injuries were reported as early as 3000 BC in the Edwin Smith Surgical Papyrus. Ancient Greek chronicles reveal that they had anatomic knowledge of the thoracic structures. Even in the ancient world, most of the therapeutic modalities for chest wounds and traumatic pulmonary injuries were developed during wartime.The majority of lung injuries can be managed non-operatively, but pulmonary injuries that require operative surgical intervention can be quite challenging. Recent progress in treating severe pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 39 publications
2
25
0
4
Order By: Relevance
“…In the present study, the management modalities correlate with those reported in the literature (16,17). Most penetrating chest injuries do not require major operative interventions, and several patients are managed with observation and serial evaluation using radiography or simple tube thoracostomy (11).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the present study, the management modalities correlate with those reported in the literature (16,17). Most penetrating chest injuries do not require major operative interventions, and several patients are managed with observation and serial evaluation using radiography or simple tube thoracostomy (11).…”
Section: Discussionsupporting
confidence: 70%
“…Gunshot wounds represent the major penetrating mechanism of injury for patients requiring thoracotomy, ranging from 13% to 70% of the cases (9,16,17), as opposed to less than 10% of injuries from blunt chest trauma. On the other hand, the present study found that early thoracotomy was performed in 26.0% of penetrating injuries and in 2.8% of blunt injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic DC interventions Pneumonorrhaphy 1,7,8 After small injured vessels and bronchi within the parenchyma of a superficial pulmonary laceration are selectively ligated, the edges are approximated. Pulmonary tractotomy 1, 7Y10 The lung bridging a pulmonary parenchymal wound is divided using a GIA 55/75 vascular stapler or between two long vascular clamps and then small injured parenchymal vessels and bronchi lying underneath are selectively ligated.…”
Section: Intervention Descriptionmentioning
confidence: 99%
“…It does require more extensive preparation. It should only be utilized if the patient is hemodynamically stable, and the injury is confined to a single hemithorax [ 8 ]. Correct positioning of the patient is essential and includes lateral positioning with the iliac crest at the level of the table break and rolls or an inflated bean bag to assist in stabilization.…”
Section: Posterolateral Thoracotomymentioning
confidence: 99%